The Effect of Working Capital Management and Leverage on Value of Manufacturing Companies through Profitability Ratio - Rambe, Jerni Duma Sari; Manullang , Nova Sari; Tambunan, Daniel Ortega; Sinurat, Mangasi; Saragih, Maulana Majied Sumatrani (International Journal of Industrial Engineering, Technology & Operations Management, 2023)
A company is a group of people who are members of an organization who work to achieve certain goals. One of the most basic company goals is to obtain maximum profit or profit from the company's business activities. The purpose of establishing a company is not only to achieve maximum profit, but also aims to increase the prosperity of parties related to the company's business activities, such as shareholders and stakeholders so that the value of the company increases. The research method used is a quantitative data method. Working capital management has a positive and significant effect on firm value, leverage has no significant effect on firm value, and working capital management and leverage have no simultaneous significant effect on firm value. Company value can be used as the basis for making investment decisions because this aspect measures the ability of the company's assets to generate a return on investment made in the company's asset instruments. This study concludes that manufacturing companies listed on the Indonesia Stock Exchange will always maintain the value of the company, and this research should be a strategy or consideration for Manufacturing companies pay attention to company values in carrying out company activities. Paying attention to working capital management, leverage, profitability and especially firm value because this aspect is very attractive to investors in conducting technical analysis and predicting the movement of the company's stock price. It is interesting if the company has a good corporate value. So that investors can find out risk analysis and predict the value of the company, of course investors will be interested in investing their funds in the company.